Ascendance to Schengen: How Did the Schengen Area Effect Finland's Economy - Reyes Escalona, Daniela; Suggs, Bryce; Johnson, Sadie (My University, 2020)
While a member of the European Union since January 1, 1995, Finland made a significant step toward greater openness when it joined the Schengen Area on March 25, 2001. The Schengen Area is the world's largest VISA free zone. Member countries agree to abolish border controls which allows the unrestricted flow of people between member countries and establish common rules for external borders. Schengen member countries also agree to ensure cooperation between police and the judicial systems of the member countries. Using data from Quarter 1 1990 through Quarter 3 2019 from Eurostat, this study examines whether becoming a member of the Schengen Area significantly changed Finland’s long-run economic growth rate. The study also examines whether becoming a member of the Schengen Area significantly changed the statistical relationship between Finland’s economic growth rate and the change of its unemployment rate. The results find that while joining the Schengen Area did not change Finland's long-run growth rate, it did significantly reduce the negative relationship between the growth rate and the unemployment rate change. Before joining the Schengen area, a 1% increase of the unemployment rate reduced Finland's growth rate by .72%. After joining the Schengen Area, a 1% increase of the unemployment rate reduced Finland's growth rate by 0.14%. Finland’s long-run growth rate remained unchanged at 2.9%.